The Relationship between Food Waste and Nutritional Status of Toddlers in Abang District Karangasem - Wulandari, Kadek Nuansa Putri; Sutiari, Ni Ketut; Utami, Ni Wayan Arya (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Food intake is a basic human need, yet each individual has different eating habits. Some people consume excessive amounts of food, increasing their risk of obesity, while others experience food shortages or frequently leave uneaten food that ends up as food waste. These behaviors are influenced by excessive food purchasing, limited knowledge of food storage and processing, poor food management, food quality and taste, limited time for cooking, and low environmental awareness. Household food waste reflects inefficient food utilization, which may affect the nutritional intake of toddlers, particularly in food-insecure areas such as Abang District, Karangasem Regency. This study employed a cross-sectional design with a sample of 104 toddlers selected through multistage sampling. Nutritional status data were collected through anthropometric measurements, while food waste behavior data were obtained using a food waste behavior questionnaire. The results showed that most toddlers had normal nutritional status, whereas household food waste behavior was still relatively poor. Bivariate analysis revealed a significant relationship between food waste behavior and the nutritional status of toddlers based on the weight-for-age index (WAZ) (p=0.043), and multivariate analysis showed that food waste behavior had a significant effect on the nutritional status of toddlers (p=0.020). It can be concluded that food waste behavior is significantly associated with the nutritional status of toddlers. Therefore, educational efforts and interventions are needed to reduce household food waste in order to support improvements in toddlers’ nutritional status.